INFILTRATION ANALYSIS AND CHARACTERIZATION OF PHYSICALCHEMICAL PARAMETERS OF GROUNDWATER IN JAYAMEKAR AREA AND ITS SURROUNDINGS, WEST BANDUNG REGENCY, WEST JAVA PROVINCE - Fakhrun Abdillah, Muhammad
Research on infiltration and characteristics of physical-chemical parameters of groundwater is carried out on unconfined aquifers from weathering soils in the Jayamekar and surrounding areas. The research area consists of Aquifer-Aquiclude of Folded Sandstone-Limestone Unit, Aquifer-Aquiclude of Tuff Unit, and Aquifer-Aquiclude of Volcanic Breccia Unit. The pattern of groundwater flow generally leads to south-southeast with hydraulic gradient value of 0.04 m/L. The measurement of infiltration rate is carried out 15 times in different locations. Infiltration rate in weathered soil from Aquifer of Folded Sandstone-Limestone Unit has a value of 8.58 cm/hour or Moderate Fast. Whereas in weathering soil from Aquifer of Tuff Unit has a value of 23.98 cm/hour or Fast. In addition, in the weathering soil from Aquifer of Volcanic Breccia Unit has a value of 25.08 cm/hour or Fast. The results show the physical parameters of groundwater in weathering soil from Aquifer of Folded Sandstone-Limestone Unit has temperature values of 280C - 300C, Total Dissolved Solids (TDS) is 203 ppm - 226 ppm, and pH 6.07-6.64. Whereas in groundwater in weathering soil from Aquifer of Tuff Unit has temperature values of 280C - 300C, TDS 203 ppm - 226 ppm, and pH 6.07-6.64. As well, groundwater in weathering soil from Aquifer of Volcanic Breccia Unit has temperature values of 280C - 300C, TDS 27 ppm - 45 ppm, and pH 5.63-6.84. All of three units have no smell and tasteless. Based on these physical parameters, the available values indicate groundwater is fresh water and still meets the provisions of physical parameters of potable water. The results also show that groundwater is included in the upper zone and the groundwater flow system is local. For chemical parameters of groundwater, especially groundwater chemical facies, it can be described by the predominance of the major ion content such as the Aquifer of Folded Sandstone- Limestone Unit, namely calcium (Ca2+), chloride (Cl-), and bicarbonate (HCO3 -) which are included in calcium chloride (CaCl2) and calcium bicarbonate (Ca(HCO3)2) facies. As well, in weathering soil from Aquifer of Tuff Unit and Volcanic Breccia Unit shows the dominance of calcium (Ca2+) and chloride (Cl-) ions which are included in the facies of calcium chloride (CaCl2). The research area is divided into five rock units, namely Limestone Unit, Sandstone Unit, Tuff Unit, Volcanic Breccia Unit, and Alluvial Unit. The geological structure formed in the study area are anticline and syncline with the direction of the northeast – southwest fold axis.